Economic analysis of law and alternative dispute resolution in consumer disputes: efficiency and fairness - Castillo Lopez, José Manuel CASTILLO LÓPEZ (Revista Jurídica Portucalense, 2022)
In recent decades, various public and private institutions have pointed out the deficiencies in the Administration of Justice in Spain and, consequently, reform proposals have been made, including the establishment of alternative dispute resolution systems (ADR) that , inescapably, they arise between people. Both, in reality, represent two ways of solving social conflicts, of doing justice, but in which the observance of the legal guarantees of citizens must be reserved to the Judicial System, as an ordinary procedure. Therefore, ADRs are not competing mechanisms in the sense of exclusive or alternative, but complementary, which open the possibility for companies and consumers to use extrajudicial means to resolve their conflicts. Mediation in consumer activities presents in relation to the traditional and ordinary system of justice a series of elements that advise its use as they can contribute to the improvement of efficiency and equity in the management of Justice in Spain and, therefore, to the increase of the well-being of the majority of the population. We refer, above all, to the lower cost, shorter duration, greater transparency and, therefore, predictability in the resolution of conflicts and, in addition, these advantages will increase with the incorporation of digital platforms to the management of these procedures.